2020
DOI: 10.5430/ijfr.v11n3p73
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Assessment Models of Retail Microfinancing: The Case of a Malaysian National Savings Bank’s Branch

Abstract: Internal ratings have been used by banks to evaluate the creditworthiness of their borrowers with diverse practices. This research aims to analyse the practice of assessing (or predicting) the credit performance of microfinancing loans of a Malaysian bank and to suggest how the existing performance of credit assessment model can be improved. Logistic regression was used to investigate the predictive ability of information on business operators’ management and accounting skills as factors to predict default ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In terms of the nature of its business, credit risk is one of the major risks faced by banks. By effectively managing credit risk exposures, banks not only support the viability and profitability of their businesses but also contribute to systemic stability and the efficient allocation of capital in the economy (Abdullah et al 2020). "Defaults by a small number of customers can be very costly for banks" (Khalid et al 2021).…”
Section: Credit Risk Management and Performance Of Commercial Banksmentioning
confidence: 99%
“…In terms of the nature of its business, credit risk is one of the major risks faced by banks. By effectively managing credit risk exposures, banks not only support the viability and profitability of their businesses but also contribute to systemic stability and the efficient allocation of capital in the economy (Abdullah et al 2020). "Defaults by a small number of customers can be very costly for banks" (Khalid et al 2021).…”
Section: Credit Risk Management and Performance Of Commercial Banksmentioning
confidence: 99%
“…Generally, performance management within the supply chain context has received much attention in the literature. Some studies have highlighted the importance of performance management as a key tool for managing supply chain (Chiarini & Vagnoni, 2015;Hong et al, 2018), enhancing SCM activities and relationships (Mouritsen et al, 2001;Hofmann & Kotzab, 2010), reducing relational risk or promoting greater cooperation through trust building (Coletti et Asian Journal of Business and Accounting 15(1), 2022 al., 2005;Abdullah et al, 2020). As pointed out by Velayutham et al (2021), the recent Covid-19 pandemic has uncovered the lack of visibility as a problem in certain supply chains and they identified that accounting information can be used to increase the visibility throughout the supply chain.…”
Section: Information Sharing and The Role Of Accountingmentioning
confidence: 99%
“…Classical credit reporting, which is primarily focused on financial data, may only provide such good assessment of SMEs that are restricted in financial data but flourishing in non-financial data, like big data from business, government, social media, and networks (Yadi et al, 2019). The significance of identifying financial and non-financial indicators to evaluate the credit risk associated with microfinance loan applications is inevitable (Abdullah et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%